Current Conditions and Policy Frameworks of Agri-Food Systems Transformation - Riemer, Olivia; Shah, Tavseef Mairaj; Zitterbarth, Sarah; Caron, Patrick; El Hage Scialabba, Nadia; Hamm, Michael; Kimani-Murage, Elizabeth; Martínez-Cruz, Tania; Merrigan, Kathleen; Mooney, Pat; Fleckenstein, Martina; Mulet, Michael; et al. (Think Tank for Sustainability, 2023)
The first report, Current Conditions & Policy Frameworks of Agri-Food Systems Transformation takes a systems view of the aforementioned challenges. It outlines the ecological, health and social challenges of current agri-food systems and analyses how these interact with the 4 Cs (Climate, Covid-19, Conflict and Costs). Furthermore, the report reviews the existing policy frameworks at the international level that inform the direction of, and could potentially steer, the transformation of agri-food systems.